2016
DOI: 10.1002/art.39441
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Granulocytic Myeloid‐Derived Suppressor Cells in Lupus‐Prone Mice Linked to Reactive Oxygen Species–Dependent Extracellular Trap Formation

Abstract: Objective. Emerging evidence supports a crucial role of myeloid-derived suppressor cells (MDSCs) in the regulation of autoimmune diseases. However, their role in systemic lupus erythematosus (SLE) remains unknown. This study sought to address the role of MDSCs in the pathogenesis of SLE.Methods. MDSCs from (NZB 3 NZW)F1 lupusprone mice were assessed for phenotype by flow cytometry, and the function of MDSCs was analyzed by in vitro T cell proliferation assay and real-time quantitative polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…Finally, in mice, the presence of proinflammatory cytokines such as IL‐6 and TNF‐α, which are abundant in CIA sera , might influence NET formation upon PMN signaling. This is in line with our recent report in lupus‐prone mice that IL‐6 demonstrated to drive NET release by granulocytic cells .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, in mice, the presence of proinflammatory cytokines such as IL‐6 and TNF‐α, which are abundant in CIA sera , might influence NET formation upon PMN signaling. This is in line with our recent report in lupus‐prone mice that IL‐6 demonstrated to drive NET release by granulocytic cells .…”
Section: Discussionsupporting
confidence: 92%
“…Although it is becoming apparent that NETs have a significant impact on chronic autoimmune inflammatory diseases such as lupus, psoriasis, atherosclerosis, and arthritis , the mechanism involved in NET‐mediated adaptive autoimmune responses remains elusive. Herein, we provide new insights into the NETs‐mediated induction of T‐cell autoreactivity that contribute to the immunopathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Murine studies support a role for IL-6 in both the MRL/ lpr and Junb epidermal deletion models of cutaneous lupus (Cash et al, 2010; Pflegerl et al, 2009). Some have identified the importance of IL-6 in promotion of neutrophil extracellular trap formation (Vlachou et al, 2016); this phenomenon has been noted to be important in murine cutaneous lupus. A chart review performed on cutaneous lupus skin samples from our RT-PCR and immunohistochemistry data revealed a significant correlation between IL-6 levels in the skin and SS-A antibody status.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present analysis showed a positive correlation between iNOS and SLE, the source of iNOS is unknown. Recently, increasing evidence has suggested that proportions of myeloid-derived suppressor cells (MDSCs), a heterogeneous myeloid precursor, enhanced in SLE patients and mice [38,39]. Although a variety of potential mechanisms is involved in the immunosuppressive function of MDSCs, the main suppressive activity of MDSCs is associated with the secretion of arginase-1 and iNOS [30,40].…”
Section: Discussionmentioning
confidence: 99%